2020
DOI: 10.33258/birex.v2i1.698
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Fried Snacks Intake with Free Radicals and Obesity in Elementary School Children

Abstract: The increase in degenerative disease and obesity is mainly caused by lifestyle, eating pattern, and activities. Obesity can cause death throughout the world. It affected 349 million children and adolescents (5-19 years old) in 2016. The objective of this research was to find out the correlation of fried snacks intake with free radicals, and obesity. The research used quantitative method with cross sectional design. The samples were 56 students of elementary school, taken by using purposive sampling technique. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…the suggested that health workers should pay more attention to those who have 1-2 children who are motivated to participate in the family planning program and ask pregnant women to ask health workers before using family planning tools as clearly as possible so that they are expected to be able to reduce the reason for unmet need for family planning. Hidayati, et al (2020), conducted a study on correlation of fried snacks intake with free radicals and obesity in elementary school Children. They found that the increase in degenerative disease and obesity is mainly caused by lifestyle, eating pattern, and activities.…”
Section: Review Of Literaturesmentioning
confidence: 99%
“…the suggested that health workers should pay more attention to those who have 1-2 children who are motivated to participate in the family planning program and ask pregnant women to ask health workers before using family planning tools as clearly as possible so that they are expected to be able to reduce the reason for unmet need for family planning. Hidayati, et al (2020), conducted a study on correlation of fried snacks intake with free radicals and obesity in elementary school Children. They found that the increase in degenerative disease and obesity is mainly caused by lifestyle, eating pattern, and activities.…”
Section: Review Of Literaturesmentioning
confidence: 99%